1999
DOI: 10.1017/s096702629900205x
|View full text |Cite
|
Sign up to set email alerts
|

Floridean starch and carrageenan contents as responses of the red alga Solieria chordalis to culture conditions

Abstract: The influence of culture conditions on the biosynthesis and degradation of polysaccharides (starch and carrageenan) in the red alga Solieria chordalis was investigated. Following 1 week of incubation in the dark, the alga synthesized floridean starch at two irradiances, 50 and 480 µmol photons m −# s −" (400-700 nm), in nutrient-unenriched seawater. Upon transfer of these cultured algae to nutrient-enriched seawater at 50 µmol photons m −# s −" , the stored floridean starch was found to break down. "%C labelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Thus, the photosynthetic carbon was not oriented towards the synthesis of low-molecular-weight compounds but certainly aimed towards storage product like floridean starch or carrageenan. This hypothesis is supported by the study of Fournet et al (1999) which showed that S. chordalis synthesized floridean starch under the same conditions of irradiance when the alga was post-conditioned one week in the dark. After this first 24 h, the C/N ratio increased strongly to reach 1.93 (after 2.5 days) resulting in the orientation of photosynthetic carbon towards a carbonated compound, the floridoside for which the level was multiplied by 53 %.…”
Section: Effects Of Changing Culture Conditionsmentioning
confidence: 71%
“…Thus, the photosynthetic carbon was not oriented towards the synthesis of low-molecular-weight compounds but certainly aimed towards storage product like floridean starch or carrageenan. This hypothesis is supported by the study of Fournet et al (1999) which showed that S. chordalis synthesized floridean starch under the same conditions of irradiance when the alga was post-conditioned one week in the dark. After this first 24 h, the C/N ratio increased strongly to reach 1.93 (after 2.5 days) resulting in the orientation of photosynthetic carbon towards a carbonated compound, the floridoside for which the level was multiplied by 53 %.…”
Section: Effects Of Changing Culture Conditionsmentioning
confidence: 71%
“…Fig. 4a groups [29,30]. These groups appear in algal Gelidium associated with sulphated galactans of agar.…”
Section: Ftir Characterizationmentioning
confidence: 95%
“…The fragments were mixed together before being distributed to the culture flasks in order to obtain results representative of the population. We used the conditions that we had previously found as optimal for floridean starch synthesis or degradation (Fournet et al 1999). The algal fragments were placed in filtered seawater at 12°C and submitted to a 12:12 LD cycle for 20 days with an irradiance of 75 µmol photons m -2 s -1 .…”
Section: Culture Conditionsmentioning
confidence: 99%
“…Starch concentration was determined from the difference between the total glucose after amyloglucosidase hydrolysis and the free glucose in the lyophilized extract before amyloglucosidase hydrolysis. The procedure used was derived from Bergmeyer and Bernt by Fournet et al (1999).…”
Section: Floridean Starchmentioning
confidence: 99%
See 1 more Smart Citation